2021
DOI: 10.1002/cti2.1237
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis CD14+ monocytes display metabolic and inflammatory dysfunction, a phenotype that precedes clinical manifestation of disease

Abstract: IntroductionThis study investigates the metabolic activity of circulating monocytes and their impact on pro‐inflammatory responses in RA and explores whether this phenotype is already primed for inflammation before clinical manifestations of disease.MethodsBlood was collected and CD14+ monocytes isolated from healthy control donors (HC), individuals at‐risk (IAR) and RA patients. Monocyte frequency in blood and synovial tissue was assessed by flow cytometry. Inflammatory responses and metabolic analysis ± spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 86 publications
(184 reference statements)
2
48
0
1
Order By: Relevance
“…McGarry and Hanlon et al reported that CD14 + monocytes in the peripheral blood of RA patients are metabolically reprogrammed towards glycolysis ( 82 ), a key feature of trained immunity ( 48 , 65 ). Furthermore, when compared with healthy controls, monocytes from the blood of RA patients produced more TNF, IL-6 and IL-1β in response to LPS stimulation in vitro ( 82 ). These are key cytokines that are enhanced in cells that have undergone pro-inflammatory innate immune training with BCG or β-glucan ( 5 , 6 ).…”
Section: The Clinical Significance Of the Link Between Innate Immune Training And T Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…McGarry and Hanlon et al reported that CD14 + monocytes in the peripheral blood of RA patients are metabolically reprogrammed towards glycolysis ( 82 ), a key feature of trained immunity ( 48 , 65 ). Furthermore, when compared with healthy controls, monocytes from the blood of RA patients produced more TNF, IL-6 and IL-1β in response to LPS stimulation in vitro ( 82 ). These are key cytokines that are enhanced in cells that have undergone pro-inflammatory innate immune training with BCG or β-glucan ( 5 , 6 ).…”
Section: The Clinical Significance Of the Link Between Innate Immune Training And T Cellsmentioning
confidence: 99%
“…In the setting of established RA disease, the enhanced inflammatory function of monocytes may not be indicative of trained immunity, but it could also reflect chronic inflammation. To determine if these hyperinflammatory monocytes were a precipitating factor for inappropriate inflammation in people with RA, the study examined monocytes in people who were identified as being at increased risk of developing RA ( 82 ). The hyperinflammatory CD14 + cell phenotype was present in these individuals at risk of developing RA, suggesting that this trained immunity phenotype may precede clinical signs of disease and may therefore be implicated in pathology ( 82 ).…”
Section: The Clinical Significance Of the Link Between Innate Immune Training And T Cellsmentioning
confidence: 99%
See 3 more Smart Citations